Menumbuhkan jiwa entrepreneurship mahasiswa di perguruan tinggi - Supami Wahyu Setiyowati; Mochamad Fariz Irianto; Irma Tyasari; Susmita Dian Indiraswari (MBR (Management and Business Review), 2022)
The purpose of this study was to determine the entrepreneurial spirit of students and to determine the role of learning innovation on the entrepreneurial spirit of students. This research is a type of mix-method research, with the survey, interview, observation, and documentation methods. The survey was carried out by distributing questionnaires to 40 students offline. The results show that students of the Accounting study program have an entrepreneurial spirit, another finding is that learning innovation is effective for developing student entrepreneurial spirit, which is implemented in business startups as long as students are thematic KKN in the community and can improve the economy.